A physiological indicator to estimate allicin content in garlic during storage - González, Roxana Elizabeth (2013)
The aim of the present work was to evaluate the application of a physiological indicator as marker of allicin content during postharvest storage at different temperatures. Sureño INTA garlic cultivar was stored at room temperature (20C 3) and cold storage (0C 0.5). Samples were taken periodically and allicin, pyruvate content and the sprout growth were analyzed. The sprout growth was measured through of the visual index of dormancy (VID%).The results showed that regardless of storage temperature, allicin, pyruvate content and VID changed significantly during the period of the assay. For the conditions evaluated, the highest allicin content was observed at 50% and 100%VID.These facts suggest that VID% may be a suitable tool to estimate allicin level during storage